PENGUATAN SISTEM PENGENDALIAN INTERNAL BERBASIS SDM UNTUK MENINGKATKAN EFISIENSI OPERASIONAL UMKM KIBAKSO BATAM - Yuli Indah Fajar Dini; Siti Annisa Ayu Mulyani (Bajang Institute, 2026)
This community service activity addresses the operational challenges faced by Kibakso SME in Batam, particularly the absence of documented Standard Operating Procedures, manual administrative systems, and unstructured human resource control mechanisms. This activity aims to design and implement an HR-based internal control management system to enhance operational efficiency. A qualitative descriptive approach was applied through direct interviews and field observation. The resulting system encompasses operational SOPs, standardized forms, a QR Code-based employee attendance system, and a structured task distribution database. Initial implementation through socialization to the owner and employees demonstrated measurable improvements in operational regularity, role clarity, and work activity monitoring. This initiative confirms that structured HR-based internal control systems are viable and impactful solutions for SMEs seeking sustainable performance in competitive urban economies.